The Persistence of Volatility in Nifty 50 - Vevek, S.; Selvam, M.; Sivaprakkash, S. (Indian Journal of Research in Capital Markets, 2022)
The market participants trade in the Nifty index to mitigate the risk, as trading in Nifty leads to wealth and exposes the market participants to external shocks. Normally, market participants disfavor volatility as it is a serious concern. So, volatility measures the magnitude of the information’s impact on any index or stock. The unpredictability of external shock toward the market was a cause for concern because it had adverse effects on the market. The index values worldwide had been substantially sensitive to the external stock. With several factors contributing to the stock market’s performance, distilling volatility is impossible. In addition, the COVID-19 pandemic was the starlight in fuelling the unpredictability in the security markets. The study empirically investigated the impact of events (shocks) on the Nifty 50 index. To achieve our objective, we applied the GARCH model for estimating the volatility of daily returns of the closing price of the Nifty 50 index from January 1, 2019 to December 15, 2021. A total of 732 observations were sourced from the NSE website and transformed into natural log returns for volatility pattern analysis. The findings revealed that the Indian secondary market had experienced unanticipated volatility during the study period. The shock was strong even when the positive information arrived. The existing negative information had a stronger hold over the market movement.